Who are the "Immigrants"?: How Whites' Diverse Perceptions of Immigrants Shape Their Attitudes. (8th October 2022) - Flores, René D; Azar, Ariel
Abstract: Past scholars find that there is a public consensus in the United States on the traits of ideal immigrants. Nevertheless, is there also a consensus on the perceived traits of actual immigrants living in the country? Further, are these perceptions attitudinally consequential? We find no consensus among whites on the composition of the immigrant population in the United States. Further, the immigrant traits they perceive are correlated in specific stereotypical patterns we label "immigrant archetypes." Using latent class analysis, we find five archetypes. Two of them are extreme—one represents a high-status, documented non-Latino immigrant, which is associated with the most positive immigration attitudes. The other extreme represents a low-status, undocumented Latino man, which is associated with the most restrictionist immigration views. Nevertheless, a second Latino archetype, a better-educated and documented Latina woman working to support her family, is correlated with more positive attitudes than her male counterpart. Archetypes do not seem entirely rooted in objective reality and are stronger predictors of immigration attitudes than most other independent variables. Their existence has significant implications for public opinion dynamics. When researchers, politicians, or journalists reference a single immigrant trait, they may knowingly or unknowingly conjure up entire archetypes in people's minds.